The Origin of Thinking: Restoring the Living Roots of Rational Consciousness - Parry, Glenn Aparacio (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
<!--[if gte mso 9]> <![endif]-->Certain tacit assumptions of modernity are jeopardizing the future of humanity and the planet-assumptions around what constitutes life; the nature of being human; rational thought; and our view of time and progress. This paper examines the origins of why we think the way we do today and how we can reclaim the living roots of consciousness (even as they are seemingly lost or obsolete). In so doing, we restore our full humanity and help restore the Earth. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->